Critical Overview of the Contents of Risk Management Plans for Medicines - T. M. Bukatina; E. V. Shubnikova (Безопасность и риск фармакотерапии, 2022)
The pharmacovigilance system plays one of the key roles in ensuring safety and efficacy of medicine use. The risk management process helps to ensure the most favourable benefit/risk ratio of a medicine or combination of medicines both for the target populations and the general public. Unavailability of a risk management process for medicines may adversely affect the health of the general population. One of the major documents in medicine risk management is the risk management plan (RMP).The aim of the study was to analyse compliance of RMPs submitted as part of registration dossiers with the requirements of the Eurasian Economic Union (EAEU), and to analyse problems arising during their preparation.Materials and methods: the authors analysed 200 RMPs submitted from January 1 until August 31, 2021.Results: it was determined that the most frequent mistakes made by pharmacovigilance officers are related to medicine summaries in RMPs covering several medicines, medicine safety specification parts of RMPs, description of risks in the pharmacovigilance plan and description of risk minimisation measures, and insufficient representation of the key elements of the medicine efficacy and safety overview in the RMP summary. For instance, RMPs often lack information on the epidemiology of indications for target populations in the EAEU, or RMPs may lack some of the major risks reflected in the patient information leaflets, or lack assessment of safety risk minimisation actions, etc.Conclusions: proper preparation of RMPs that would comply with the EAEU Good Pharmacovigilance Practice is inconceivable without further professional training of pharmacovigilance officers.